2010
DOI: 10.3892/ijo_00000527
|View full text |Cite
|
Sign up to set email alerts
|

Timing of surgery and radiotherapy in the management of metastatic spine disease: A systematic review

Abstract: Abstract. The last decade has witnessed a dramatic change in management of metastatic spine disease, with an increased role for surgery and emerging use of stereotactic radiotherapy, often in combination. Patients may be treated with radiotherapy followed by surgery, or have surgery and then adjuvant radiotherapy. In both cases, the surgeon and oncologist need to select the optimal timing for surgery and radiotherapy to minimize wound complications while obtaining maximum oncolytic effects. The purpose of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Dorsal spinal decompression and stabilization are the most frequent surgical techniques used to treat metastatic disease of the thoracic and lumbar spine 1,2,3,4,5,6,7,8,9,10 . For patients with a solitary spinal metastasis without vertebral canal invasion and who are in good general health with a long life expectancy, tumor resection through en bloc spondylectomy/total vertebrectomy with primary stabilizing instrumentation has been suggested 9,10,11,12,13 . A recent paper reported that candidates for en bloc spondylectomy are not frequently encountered 14,15,16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dorsal spinal decompression and stabilization are the most frequent surgical techniques used to treat metastatic disease of the thoracic and lumbar spine 1,2,3,4,5,6,7,8,9,10 . For patients with a solitary spinal metastasis without vertebral canal invasion and who are in good general health with a long life expectancy, tumor resection through en bloc spondylectomy/total vertebrectomy with primary stabilizing instrumentation has been suggested 9,10,11,12,13 . A recent paper reported that candidates for en bloc spondylectomy are not frequently encountered 14,15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of vertebral involvement, vertebral canal invasion, neurological status, general health status, and malignancy prognosis determined by primary tumor histology are paramount factors for surgical planning and definition of therapeutic targets 6,7,8,9,10 .…”
mentioning
confidence: 99%
“…Despite the relevance of this topic, the timing between surgery and RT has not yet been investigated thoroughly. Itshayek et al (46) recommended a minimum interval of 1 week between pre-operative or post-operative RT and surgery based on a literature review (46). When urgent surgery is indicated after RT, Ghogawla et al (47) have reported a wound complication in 46% of cases when the procedure is done within a week from RT.…”
Section: Treatmentmentioning
confidence: 99%
“…Precise targeting is limited with conventional EBRT and, as a consequence, the tolerance of the spinal cord limits the radiation dose to the vertebral body with pain relief achieved in only 60% of patients and local tumor control in only 30% of the patients after 1 year (57). Furthermore, to reach adequate radiation doses to the metastasis, hotspots of >120% of the prescribed dose are common in the subcutaneous tissues, which impairs wound healing (8). As such, a minimum time interval of 1–2 weeks between surgery and EBRT is considered necessary but thereby also delays radiotherapy-induced pain relief (8).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to reach adequate radiation doses to the metastasis, hotspots of >120% of the prescribed dose are common in the subcutaneous tissues, which impairs wound healing (8). As such, a minimum time interval of 1–2 weeks between surgery and EBRT is considered necessary but thereby also delays radiotherapy-induced pain relief (8).…”
Section: Introductionmentioning
confidence: 99%